Measures affecting the agreed profit sharing ratio in joint ventures financed by Islamic banks: a Shari’ah based evaluation - Sadique, Muhammad Abdurrahman (2009)
Equity participation in joint ventures as envisaged in shari‘ah comprises a business relationship based on mutual sharing of gains and liability. Such partnerships established among individuals as well as commercial enterprises generally seek to realise the possibility of unlimited gains for each partner, without the encumbrance of ensuring a preset capital return to a single partner. Islamic banks need to adopt an approach similar to these and desist from furthering their identity as lending institutions, a pioneer step towards which goal would be upholding a proper profit and loss sharing mechanism. For realising the benefits of equity financing, its operation should not be hindered through measures that strip it of its characteristics. A central pillar of the equity structure is the unbridled operation of the profit sharing ratio. Restriction of its application to a stipulated level of profits, thereby enabling a partner to claim unlimited profits while the profit share of the other is restricted to a maximum ceiling cannot be regarded to be consistent with the theory of equity participation. Any measure that curtails the free operation the profit sharing mechanism could result in defeating the objectives of equity financing. Similarly, a provision that envisages the possibility of adjusting the profit sharing ratio prior to liquidation does not seem appropriate in the prevalent environment of interest based banking, and could be easily misused. While these measures could realise some temporary benefit to Islamic banks, they may become deep-rooted in the concept of equity financing itself, thus making it operate subservient to debt financing norms.